The Transformation of the Self in a Secular Culture. A Discussion on Pannenberg’s Position (Global Journal of Human-Social Science, 2020)
The topic under consideration is the change in the human self understanding in the secular culture according to Pannenberg a contemporary thinker of great rational strength The author poses some questions which underline the ambiguities of secularization and its historical causes The result has been a new model of manAccording to Pannenberg the impact of the 17th- 18th centuries Modern ideas over the concept of the self has been great
Keywords: postmodernism; Pannenberg; emancipation; autonomous self; secularization; image of god